a, X * \(\dfrac{3}{4}\)+X : 4= \(\dfrac{3}{7}\)
c, 1,5-( X: 0,5 + \(\dfrac{5}{8}\)) : \(\dfrac{3}{2}\) = 0
b, ( \(\dfrac{7}{20}\) + \(\dfrac{1}{2}\) - X) : \(\dfrac{64}{15}\)= \(\dfrac{9}{128}\)
Có ai biết 3 câu trên ko? Giúp Mình với.
Ghi lời giải cụ thể nhé!
a: \(x\times\dfrac{3}{4}+x:4=\dfrac{3}{7}\)
=>\(x\times\left(\dfrac{3}{4}+\dfrac{1}{4}\right)=\dfrac{3}{7}\)
=>\(x\times\dfrac{4}{4}=\dfrac{3}{7}\)
=>\(x=\dfrac{3}{7}\)
b: \(\left(\dfrac{7}{20}+\dfrac{1}{2}-x\right):\dfrac{64}{15}=\dfrac{9}{128}\)
=>\(\left(\dfrac{7}{20}+\dfrac{10}{20}-x\right)=\dfrac{9}{128}\times\dfrac{64}{15}\)
=>\(\dfrac{17}{20}-x=\dfrac{1}{2}\times\dfrac{3}{5}=\dfrac{3}{10}\)
=>\(x=\dfrac{17}{20}-\dfrac{3}{10}=\dfrac{17}{20}-\dfrac{6}{20}=\dfrac{11}{20}\)
c: \(1,5-\left(x:0,5+\dfrac{5}{8}\right):\dfrac{3}{2}=0\)
=>\(\left(x:0,5+\dfrac{5}{8}\right):\dfrac{3}{2}=1,5\)
=>\(x:0,5+\dfrac{5}{8}=1,5\times\dfrac{3}{2}=\dfrac{9}{4}\)
=>\(x:0,5=\dfrac{9}{4}-\dfrac{5}{8}=\dfrac{13}{8}\)
=>\(x=\dfrac{13}{8}\times\dfrac{1}{2}=\dfrac{13}{16}\)